2021
DOI: 10.1038/s41598-021-02075-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum FGF21 levels are altered by various factors including lifestyle behaviors in male subjects

Abstract: Fibroblast growth factor (FGF) 21 has various functions, including glucose and lipid metabolism. This cross-sectional study aimed to investigate specific conditions that might influence the functions of FGF21. 398 men who underwent a health examination were enrolled in this study. Physical and biochemical parameters and information on several lifestyle behaviors were obtained from all subjects. FGF21 levels correlated with age, body mass index (BMI), waist circumference (WC), systolic blood pressure (SBP), dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
2
6
0
2
Order By: Relevance
“…Serum sACE2 levels showed no significant differences with age. On the other hand, FGF21 levels significantly increased with age, consistent with our previous reports ( 23 ). BMI was significantly lower in the 30–39 age group.…”
Section: Resultssupporting
confidence: 93%
“…Serum sACE2 levels showed no significant differences with age. On the other hand, FGF21 levels significantly increased with age, consistent with our previous reports ( 23 ). BMI was significantly lower in the 30–39 age group.…”
Section: Resultssupporting
confidence: 93%
“…According to our results, FGF21 expression rise was also significantly correlated to high AST and high ALT. Nakanishi et al supported this result in their study which showed that FGF21 level was remarkably associated with AST and ALT elevation ( Nakanishi et al, 2021 ). This emphasizes FGF21 role as an ameliorating agent which its production increases in liver injuries.…”
Section: Discussionmentioning
confidence: 80%
“…Consistently, we found that physical activity levels were higher in the NA group than in the AN group. Additionally, the FGF‐21 level has been shown to be increased by smoking, 35 and we speculate that differences in smoking rates across study groups may have caused intergroup differences in circulating FGF‐21 levels. We observed a trend towards higher smoking rates in the AN group and lower smoking rates in the NA group.…”
Section: Discussionmentioning
confidence: 86%